STRATEGI KOMISI PEMILIHAN UMUM KABUPATEN PANDEGLANG UNTUK MENINGKATKAN PARTISIPASI PEMILIH DALAM PILKADA SERENTAK DI KABUPATEN PANDEGLANG TAHUN 2020 - Sukri Wijaya; Suwaib Amiruddin; Ayuning Budiati (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The problem with this research is that the participation of the people of Pandeglang Regency in the 2020 elections has not reached the target expected by the Pandeglang Regency KPU; the low level of community participation in several sub-districts in Pandeglang Regency in casting their right to vote; and the lack of socialization carried out by the Pandeglang Regency KPU in an effort to increase voter participation in Pandeglang Regency. The lack of coordination between the KPU of Pandeglang Regency and the DISKOMINFO Service regarding the use of social and electronic media has not been maximized in facilitating the delivery of information about the regional elections. The purpose of this study is to explain and describe how the Pandeglang Regency KPU Strategy will increase voter participation in the simultaneous local elections in Pandeglang Regency in 2020. This research uses the theory of SWOT analysis techniques according to Kotler (2008: 88). The method used in this research is descriptive-qualitative. The results showed that the strategies used by the Pandeglang Regency KPU to increase voter participation included: mutual cooperation between Pandeglang Regency KPU members in conducting elections; continuous technical guidance and training to improve the performance of regional elections in Pandeglang Regency in 2020; Utilizing electronic media and internet media in validating voter data and serving the public to maximize socialization at various levels of society The achievement of this strategy that has not been maximized is inseparable from the limited human resources, limited budget of the KPU, Pandeglang Regency KPU only relying on conventional socialization, Pandeglang Regency KPU not utilizing social media in outreach, limited facilities and infrastructure, and there are still many DPT problems.